2003
DOI: 10.1177/0269881103174015
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Effects of a Single Dose of Ecstasy (MDMA) on Psychomotor Skills and Attentional Performance

Abstract: Ecstasy (3,4-methylenedioxymethamphetamine, MDMA) is a psychoactive recreational drug widely used by young people visiting dance parties, and has been associated with poor cognitive function. The current study assessed the influence of a single dose of MDMA 75 mg and alcohol 0.5 g/kg on cognition, psychomotor performance and driving-related task performance. Twelve healthy recreational ecstasy users participated in an experimental study conducted according to a double-blind, double-dummy, placebo-controlled th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
7
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 35 publications
(41 reference statements)
5
61
7
2
Order By: Relevance
“…Eleven tests in the attention domain were evaluated, but none of them had generated any significant effect. In the executive function domain, the literature search yielded only one study by Lamers et al (2003), which reported no effect of MDMA on visual search, planning, or retrieval from semantic memory. Surprisingly, there are no studies about the acute effects of MDMA on memory, although cross-sectional studies into the long-term effects of ecstasy on human cognition most consistently report this domain to be impaired (Verbaten 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven tests in the attention domain were evaluated, but none of them had generated any significant effect. In the executive function domain, the literature search yielded only one study by Lamers et al (2003), which reported no effect of MDMA on visual search, planning, or retrieval from semantic memory. Surprisingly, there are no studies about the acute effects of MDMA on memory, although cross-sectional studies into the long-term effects of ecstasy on human cognition most consistently report this domain to be impaired (Verbaten 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that selectivity of MDMA effects have been reported in other psychological domains as well. Lamers et al (2003) demonstrated that a single dose of MDMA produced dissociable effects on psychomotor skills and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a controlled study has been conducted to evaluate impairment of driving-related attention and psychomotor skills after a single recreational dose of MDMA, the most widely abused designer drug. The achiral analytical data from 4 biological matrices (11 ) as well as the results on cognitive and psychomotor performance tests have been published (13 ). The study also investigated the influence of MDMA on several physiologic and mood indices (14 ).…”
mentioning
confidence: 99%